Dari Mitos Menstrual Taboo Ke Dunia Kecantikan dan Fashion - Yuswati, Yuswati (Musawa Jurnal Studi Gender dan Islam, 2007)
Menstrual Taboo is a never ending phenomenon. We can study about it from different points of view: medical, psychological, anthropological, mythological, theological as well as ideological perspectives. Talking about the popular myth of menstrual taboo, there are "evil eyes", "huts" etc, that protect women in her monthly period. Right now, the myth of menstrual taboo has deviated into the farms of menstrual creations such as the present of cosmetology like Kohl, eye liner, shoes and fashion. Jilbab, as a code of women's dress has actually been widely practiced far before emergence of Islam. Nevertheless, when Islam come to be spread, jilbab was associated with several superstitions, one of them is menstrual taboo. In the last ten years, Jilbab for teenagers and young women has been "booming in Indonesia. Many schools from elementary to university, and governmental offices as w~U have made jilbab as part of their official uniforms.